Picture Books for Children : Fiction, Folktales, and Poetry. - Northrup, Mary. (Chicago : ALA Editions, 2012)
Providing descriptive annotations of the best children's picture books published in the last decade, this comprehensive overview is perfect for librarians, teachers, parents, daycare providers, and anyone who works with young children.
Preface; Chapter 1: The Picture Book: Where Words and Art Come Together; Chapter 2: My Family and Myself; Chapter 3: In My Community; Chapter 4: Out in the World; Chapter 6: Folktales and Fairy Tales; Suggested Resources; Appendix 1: Picture Books about Art; Appendix 2: Self-Referential Picture Books; Illustration Credits; Index.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Picture books for children -- Bibliography; Illustrated children's books -- Bibliography; Children -- Books and reading -- United States; Livres d'images pour enfants -- Bibliographie; Livres illustrés pour enfants -- Bibliographie; Enfants -- Livres et lecture -- États-Unis.; REFERENCE -- Bibliographies & Indexes; Children -- Books and reading; Illustrated children's books; Picture books for children; United States; Bibliographies